The Contribution of Leadership Behavior through Work Environment and Individual Characteristics toward Lecturer Job Satisfaction - Abdullah, Abdul Haris (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
This research is essential because the lecturers’ job satisfaction as the leading factor in higher education activities requires adequate attention. Attention should be paid through measured research to produce reliable decisions. Therefore, this research aims to examine and measure the variables of leadership behavior, work environment, and individual characteristics to know the appropriate treatments to increase lecturer job satisfaction. The research utilized the survey design on the civil servant lecturers. The sampling technique used was a simple random sampling without considering strata because the respondents were almost homogeneous. The instruments were based on theory and expert recognition. The measurement and testing were performed using structural equation modeling (SEM), and the data analysis technique was assisted by SmartPLS 3 software. The results showed that either partially or through mediation, leadership behavior, work environment, and individual characteristics posed positive and significant contributions to lecturer job satisfaction.